2015
DOI: 10.1038/jid.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

Capsiate Inhibits DNFB-Induced Atopic Dermatitis in NC/Nga Mice through Mast Cell and CD4+ T-Cell Inactivation

Abstract: Capsaicin has many biological effects, such as antioxidant, anticancer, and antiangiogenic effects, but it is rarely used because of its high pungency. Capsiate, a nonpungent capsaicin analog, also has multiple biological effects, similar to those of capsaicin, but does not cause irritation. However, the effect of capsiate on allergic responses and immune cells has not been well studied. In this study, we investigated the effect of capsiate on atopic dermatitis, mouse CD4+ T cells, and mast cell activation. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…CD4+ T cells and mast cells are known as key factors in allergic inflammatory diseases. AD mouse model contains increased CD4+ T cell [ 30 , 31 ]. DNCB-induced AD mouse model showed severe AD symptoms, increase in mast cells, epidermal hyperplasia and elevation of serum IgE levels.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ T cells and mast cells are known as key factors in allergic inflammatory diseases. AD mouse model contains increased CD4+ T cell [ 30 , 31 ]. DNCB-induced AD mouse model showed severe AD symptoms, increase in mast cells, epidermal hyperplasia and elevation of serum IgE levels.…”
Section: Discussionmentioning
confidence: 99%
“…Spicy foods contain capsaicin, the natural ligand of transient receptor potential vanilloid 1 (TRPV1) receptors on nociceptive afferent C-fibres. The increased density of sensory fibres expressing TRPV1 receptors reported in patients with FGIDs and visceral hypersensitivity,28 the genetic polymorphism of TRPV1 gene in FD,29 the potential TRPV1 sensitisation in patients with IBS,30 the close proximity of MCs to TRPV1 expressing sensory nerve fibres and the ability of capsaicin to modulate MCs31 all suggest that transmission of pain signals, including those generated by spicy foods, may be enhanced in FGIDs. In contrast, desensitisation of afferent terminals by a high capsaicin diet seems also plausible, as one study reported beneficial effects on abdominal bloating and pain in response to the ingestion of encapsulated red pepper for 6 weeks in IBS 32…”
Section: Factors and Mechanisms Underlying MC Activation In The Gutmentioning
confidence: 99%
“…Our results showed that DNFB induced not only initial scratching but also long-lasting spontaneous scratching that lasted at least 2 weeks after the cessation of the DNFB application. Notably, DNFB, as a hapten, is usually sensitized and then challenged to induce an immune response (Kim et al, 2015;Lee et al, 2015). In our study, mice showed quick scratching responses and spinal cord ERK activation within minutes after DNFB administration, indicating that DNFB may directly or indirectly act on neuronal fibers in the skin to generate neuron-based responses that are independent of the immune activity.…”
Section: Discussionmentioning
confidence: 58%
“…Although they have different etiologies and distributions, both diseases are accompanied by chronic itch. DNFB is widely used for sensitization and challenging to induce allergic dermatitis in mouse models (Jin et al, 2009;Kim et al, 2015;Lee et al, 2014Lee et al, , 2015. In addition, repetitive challenging induces human atopic dermatitisÀlike pathogenesis in mice (Miyamoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%